Companyganj Health Project : evaluation report, September 1973-August 1978 (Christian Commission for Development in Bangladesh, 1978)
Report of an integrated health and family planning project in Companyganj Thana of Noakhali District under the joint auspices of the Govt. of Bangladesh and the Commission.